Plumsteadia pedicellata sp. nov.: A new glossopterid fructification from La Golondrina Formation (Guadalupian-Lopingian), Santa Cruz Province, Argentina - Cariglino, Barbara (2009)
A new specimen of glossopterid fructification - Plumsteadia pedicellata - from the Permian of La Golondrina Basin, in Santa Cruz Province, Argentina, is described. The fructification has ?ovule scars, and is attached to a Glossopteris leaf. This represents the first Argentinean record of glossopterid fructification in organic connection with its leaf, as well as the first record of Plumsteadia for Argentina. © 2009 Elsevier B.V. All rights reserved.